Aplikasi R Biblioshiny dalam Mengungkap Trend Riset Pembelajaran Berbasis ICT : Kajian Scientometrik - Alexander Sardi (FKIP Universitas Tanjungpura, 2022)
This study aims to determine the development of ICT Literacy research trends published by leading journals. The data analyzed consisted of 1778 indexed research publications. The data is then processed and analyzed using the R Bibliometric application to find out the bibliometric map of the ICT Literacy. The results showed that the number of publications on the ICT Literacy had increased significantly per year. The most types of documents that analyze ICT Literacy are journaled articles with 1068. The most popular author is Scherer R, and the most popular keywords are ICT, Literacy dan Digital. The trend analysis shows that ICT Literacy need to be developed considering the need for adapted with the demands of a technological world.